2019
DOI: 10.3390/min9080500
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study on the Electronic Structure and Floatability of Rare Earth Elements (La, Ce, Nd and Y) Bearing Fluorapatite

Abstract: Calcium atoms are often replaced by rare earth elements (REEs) in the lattice of fluorapatite (Ca10F2(PO4)6), making the phosphate ore an important potential rare earth resource. In this paper, the electronic properties of REEs (La, Ce, Nd and Y) bearing fluorapatite crystals have been investigated by density functional theory. Results of calculation indicated that the existence of REEs increased the cell parameters of fluorapatite in varying degrees. The REEs substitution made the Fermi level of fluorapatite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…When Ca2 was replaced by La, Ce, Nd, and Y, the overall bonding strength increased, but the bonding strength between RE-O1/O2/O3 and RE-F varied greatly. The results of Mulliken population, charge density and differential charge density obtained in our paper were compared with the results of previous literature (Wang et al, 2019). Both papers showed that after the replacement of rare earths at the Ca site, the covalency of RE-O and RE-F was enhanced compared with Ca-O and Ca-F, the difference was that the previous research only focused on the Ca2 site, while the Ca1 and Ca2 sites were analyzed in detail in our paper.…”
Section: Analysis Of Mulliken Populationmentioning
confidence: 63%
See 1 more Smart Citation
“…When Ca2 was replaced by La, Ce, Nd, and Y, the overall bonding strength increased, but the bonding strength between RE-O1/O2/O3 and RE-F varied greatly. The results of Mulliken population, charge density and differential charge density obtained in our paper were compared with the results of previous literature (Wang et al, 2019). Both papers showed that after the replacement of rare earths at the Ca site, the covalency of RE-O and RE-F was enhanced compared with Ca-O and Ca-F, the difference was that the previous research only focused on the Ca2 site, while the Ca1 and Ca2 sites were analyzed in detail in our paper.…”
Section: Analysis Of Mulliken Populationmentioning
confidence: 63%
“…Theoretically, the substitution energy was negative and REs can be substituted in FAP, and the substitution ability increased with the increase of the absolute value of substitution energy (Milojkov et al, 2020). Based on the first principle of Density Functional Theory (DFT), our research group calculated the substitution energies of La, Ce, Nd, and Y at the Ca site of FAP, which were -3.198 eV, -1.8982 eV, -3.443 eV, and 1.070 eV respectively (Wang et al, 2019). However, RE-doped FAP was a strong correlation system, and there was a strong Coulomb interaction between the electrons in the d and f orbitals of RE atoms (Xue et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The electronic structure is the most stable when the electron orbits are fully or semi filled in the same layer, so the special 4f, 5d structure of rare earth elements makes rare earth elements have similar chemical properties and different physical properties. [ 36‐37 ] Rare earth elements have high resistivity and less activity than alkali metals. With the increase of atomic number, the melting point of rare earth elements increases.…”
Section: Classification Of Rare Earth Promoted Transition Metal Sulfidesmentioning
confidence: 99%
“…The structure of TCP (Figure 6A) was calculated by using (UFF/ZDO) method with Gaussian 09 software [26,27]. The PM6 semi-empirical method was used to determine the total electron density (TED) [28,29]. The red color region indicates a high electronic density area, followed by the orange color region, which represents lower electronic density than in the red region, while the blue color area represents a low electronic density area.…”
Section: Mechanism Of Substitutionmentioning
confidence: 99%